Social Interaction and Coping Models of Child Sexual Violence in Ponorogo - Ridho Rokamah; Irma Rumtianing Uswatun Hanifa; Abdul Mun'im (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
There has been an increase in cases of sexual violence against children in the Ponorogo Regency, some of which have been made public through social media. Due to the courage of both those who commit sexual violence and the victims, this issue makes for an exciting area of research using the interaction theory, the social factor theory, and the coping theory. This study aimed to analyze the interactions of social factors and parents' coping models of the victims and perpetrators of sexual violence. It employed a qualitative approach through interviews, observations, and documentation. The findings revealed that all victims and perpetrators of sexual violence have an honest relationship with their parents. As a result, this act of sexual violence occurs due to factors in the victim's personality being close to their parents. The social factors of victims, parents, and perpetrators related to education are diverse. This crime occurs at all levels of education because, as Muzaham argues, family education is an essential element of character development that has not been implemented. The fact that all victims and perpetrators are from Java indicates a cultural shift in Javanese society due to social changes. While the concept of family is good, it falls short in building character. Focused coping is the primary mode of coping in the model. Some parents use emotional coping in the beginning, but they eventually switch to a more focused approach